Thoracoabdominal Aortic Aneurysm Repair: What Should the Anaesthetist Know? - Goel, Nitika (Turk J Anaesthesiol Reanim, 2019)
The surgical repair of descending thoracic aortic (DTA) and thoracoabdominal aortic aneurysms (TAAAs) presents one of the greatest challenges for anaesthesiologists. The challenge comes from the fine balance of complex medical issues in the setting of altered physiology that occurs during the perioperative period. Patients presenting for TAAA repair usually have multiple pre-existing comorbid conditions involving their cardiac, pulmonary and renal systems; and aneurysm repair poses a direct and immediate threat to these systems in addition to that to the gastrointestinal and neurologic systems. Operative mortality in thoracoabdominal aortic surgery is quite high to the extent of 5%–12% with a 5-year survival rate of 70%–79% for DTA aneurysm and 59% for thoracoabdominal aortic aneurysm surgeries. Complex haemodynamic changes associated with the clamping and declamping of aorta requires thorough knowledge and expertise for the management of TAAA. We present a brief review on the anaesthetic management and possible complications that anaesthetists should be aware of during TAAA repair.